Dinamika Pola Interaksi Kolaboratif Antar Aktor Dalam Tata Kelola Sampah di Kota Banjarmasin - Arbain, Taufik; Oktavianor, Tomi; Ridwan, M. Nur Iman; sugiannor, sugiannor; Fahmi, Rizal; Rahman, Raihan Pangestu (Kolaborasi : Jurnal Administrasi Publik, 2026)
This study addresses the persistent ineffectiveness of waste management in Banjarmasin, highlighted by the growing waste accumulation at the Basirih Landfill and along urban roadsides following administrative sanctions from the Indonesian Ministry of Environment. Despite a daily waste production of approximately 600 tons, regional facilities currently handle only 105 tons, signaling a critical governance gap. Employing an explanatory sequential mixed-methods design, this research analyzes waste management through the dual lenses of Network Governance and Collaborative Governance. Quantitative data were gathered from 107 diverse stakeholders, followed by in-depth qualitative interviews with key informants and Participatory Development Waste Action (PDWA) sessions. The results reveal that while there is high cognitive readiness for collaboration, the actual implementation remains at a moderate level, characterized by a "strong at the bottom, fragile in the middle" model. The governance network is currently fragmented, with interactions being largely ad-hoc and seremonial rather than institutionalized. Key barriers include a significant power imbalance dominated by the state, lack of formal institutional design, and the absence of a "metagovernor" role to synchronize bottom-up community initiatives with private sector resources. This study recommends that the Banjarmasin Municipal Government transition from a technical operator to a network steerer by establishing a permanent collaborative forum, institutionalizing long-term MOUs, and adopting an adaptive pentahelix model to bridge current collaboration gaps and ensure systemic sustainability.